2020
DOI: 10.1016/j.ymthe.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Circular RNA Sponges Act as miRNA Inhibitors to Attenuate Pressure Overload-Induced Cardiac Hypertrophy

Abstract: Circular RNAs (circRNAs) sequester microRNAs (miRNAs) and repress their endogenous activity. We hypothesized that artificial circRNA sponges (circmiRs) can be constructed to target miRNAs therapeutically, with a low dosage requirement and extended half-lives compared to current alternatives. This could present a new treatment approach for critical global pathologies, including cardiovascular disease. Here, we constructed a circmiR sponge to target known cardiac pro-hypertrophic miR-132 and -212. Expressed circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 49 publications
1
82
0
1
Order By: Relevance
“…Currently, a few studies have preliminarily used circRNA for disease treatment. Lavenniah et al constructed a circRNA sponge (circmiR) that can target the degradation of miR-132/212 family in vitro; after delivering circmiR to cardiomyocytes, the hypertrophy is weakened, and cardiac function is stable [ 111 ]. Moreover, Yang et al used rabies virus glycoprotein-circSCMH1-extracellular vesicles to selectively deliver circSCMH1 to the brain; circSCMH1 binds to methyl-CpG binding protein 2 (MeCP2) and blocks MeCP2 transporting to the nucleus, promoting the expression of downstream target genes of MeCP2, enhancing neuronal plasticity, and effectively improving the functional recovery after stroke in mice and monkeys [ 112 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…Currently, a few studies have preliminarily used circRNA for disease treatment. Lavenniah et al constructed a circRNA sponge (circmiR) that can target the degradation of miR-132/212 family in vitro; after delivering circmiR to cardiomyocytes, the hypertrophy is weakened, and cardiac function is stable [ 111 ]. Moreover, Yang et al used rabies virus glycoprotein-circSCMH1-extracellular vesicles to selectively deliver circSCMH1 to the brain; circSCMH1 binds to methyl-CpG binding protein 2 (MeCP2) and blocks MeCP2 transporting to the nucleus, promoting the expression of downstream target genes of MeCP2, enhancing neuronal plasticity, and effectively improving the functional recovery after stroke in mice and monkeys [ 112 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…In speaking of translational study of circRNAs, one study suggested that artificially designed circRNA could act as a miRNA sponge to sequester miR-122, which plays an important role in the transfer of hepatitis, to inhibit the replication of HCV ( 143 ). And another study showed that artificially designed circRNA sponging miR-132 and miR-212 could attenuate pressure overloaded-induced cardiac hypertrophy ( 144 ). These studies show a great potential for translational application of circRNAs.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…These results suggested that BC can be treated by synthesizing related circRNAs sponges. Recently, synthetic circRNA presented a new treatment approach for critical global pathologies, including cardiovascular disease, hepatitis, esophageal carcinoma, and Gastric Carcinoma ( 91 94 ). These findings establish that the design and construction of highly efficient artificial circRNAs sponges represent a novel strategy in the treatment of cancer and other diseases.…”
Section: Circrnas As Potential Therapeutic Targets For Bladder Cancermentioning
confidence: 99%